MMP1 promotes tumor growth and metastasis in esophageal squamous cell carcinoma. Issue 1 (10th July 2016) - Liu, Min; Hu, Yi; Zhang, Mei-Fang; Luo, Kong-Jia; Xie, Xiu-Ying; Wen, Jing; Fu, Jian-Hua; Yang, Hong
Highlights: MMP1 expression is increased in esophageal squamous cell carcinoma (ESCC) and associated with poor outcomes. MMP1 expression is modulated by miR-202 that is down-regulated in ESCC. MMP1 promotes cell growth and metastasis in vitro and in vivo by activation of PI3K/AKT pathway. Abstract: Matrix metalloproteinases play an essential role in the progression of esophageal squamous cell carcinoma (ESCC). Here, we show that MMP1 expression was markedly increased in a majority of ESCC compared with nontumorous tissue. High expressions of MMP1 were closely associated with lymph node metastasis, microvessel density and advanced TNM stage. Kaplan–Meier and multivariate analyses indicated MMP1 as an independent factor for overall survival in two independent cohorts of 613 patients with ESCC. In vitro studies demonstrated that MMP1 overexpression resulted in enhanced cell viability, abilities of colony formation and cell migration. The knockdown of MMP1 in ESCC cells resulted in the opposite phenomenon. Consistently, in vivo data showed that ectopic expression of MMP1 promoted tumor growth and metastasis. Further study revealed that MMP1 facilitated ESCC through the activation of the PI3K/AKT pathway. Inhibition of the PI3K/AKT pathway by LY294002 significantly attenuated MMP1-mediated cell proliferation and migration. Taken together, our data suggest that MMP1 functions as an oncogene and serves as a prognostic biomarker and a potential therapeutic target in ESCC.